Constructing the Monk: Francis Poulenc and the Post-War Context - Moore, Christopher (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2012)
Following the Second World War Francis Poulenc took a keen interest in the music of the French avant-garde and was compelled to react in both his music and his writings to the aesthetic and technical experiments of the younger generation. Although the music of composers like Olivier Messiaen and Pierre Boulez did not elicit a profound change on the substance of Poulenc’s compositional language, he did grow to the realization that the style he had embraced during the interwar period—one generally described as light-hearted and ironic—had become largely out of sync with new critical trends and concerns. Poulenc’s self-conscious aim to assert a personal form of “seriousness” in his works—one constructed with recourse to religiosity, stylistic homogeneity and the ostensibly concomitant values of sincerity and authenticity—formed the backbone of a new tone and persona that emerged following the war and which inflected his entire body of work up to his death in 1963. Poulenc’s desire to reinvent himself during this period forces us to re-examine his works, writings, and elements of his biography for the way in which they were constructed as a means of facilitating the discursive emergence of this new, more “serious,” persona.